Penggunaan Wordwall sebagai media evaluasi pembelajaran tematik pada peserta didik kelas IV di sekolah dasar - Husna, Syifa Ul; Sukarno, Sukarno; Yulisetiani, Septi (Universitas Sebelas Maret, 2023)
This study aims to describe the use, problems, and responses of students to the use of Wordwall as a medium for evaluating thematic learning in elementary schools. This research uses a qualitative approach with a case study method. The subjects in this study were teachers and fourth grade students. Collecting data in this study is by observation, interviews, questionnaires, and documentation. The validity test in this research is source triangulation. Analysis of the data in this study using the interactive model of Miles and Huberman. The results showed that the use of Wordwall as an evaluation medium for thematic learning makes it easier for teachers and students because Wordwall has many features and can be used in all subjects. The problem in designing for teachers is the need for a supportive internet network and the lack of teacher skills. Problems for students include, requiring data packets, being tense, not focused because of time constraints, feeling disturbed if the network is slow. Another obstacle is that students do not have their own handphone to be able to access Wordwall. The responses shown by students include students becoming more active, students motivated in terms of learning, students becoming competitive and enthusiastic.